Age trends in musical preferences in adulthood: 2. Sources of social influences as determinants of preferences. (June 2018) - Bonneville-Roussy, Arielle; Rust, John
Using the Music Preferences in Adulthood Model (MPAM, Bonneville-Roussy et al., 2017), an integrative model of the psychological determinants of musical preferences in adulthood, the main objective of this article is to investigate how different sources of social influences may affect age trends in musical preferences in adulthood. More specifically, we examine how the social network (such as family and peers), and psychological interpersonal dispositions (such as one's psychological tendencies towards conformity) may influence these age trends. In two studies with a total sample size of over 950 adults, we examine how social influence variables are associated with age trends in musical preferences, measured with music genres and music clips (samples of musical audio recordings). Results revealed that the social network and interpersonal dispositions are related to preferences for different musical dimensions. These relationships were stronger for the musical genres dimensions as compared with the musical clips dimensions. In addition, our findings showed that dispositions toward conformity moderate the relations between age and musical preferences in adulthood. Those results confirm that social influences, especially the interpersonal disposition towards conformity, are important in the adoption of different musical preferences as adults evolve in age. The results are discussed within a lifespan developmental psychology of music perspective.